2005
DOI: 10.1097/01.tp.0000153506.07816.f0
|View full text |Cite
|
Sign up to set email alerts
|

Induction Therapy with Basiliximab versus Thymoglobulin in African-American Kidney Transplant Recipients

Abstract: The results of our study suggest that the choice of induction agent may not have a major impact on graft outcomes in AA renal-allograft recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 27 publications
4
31
0
Order By: Relevance
“…When our study is compared with previous studies, the Thymo dosages studied here were lowered and with less complications, yet just as effectual [11][12][13][14][15][16][17]. In summary, induction therapy with either Thymo regimen for three consecutive days, with maintenance of tacrolimus, prednisone and MMF, was safe and successful with no acute rejection episodes or post-transplant complications during 6 months and subsequently at 24 months of follow-up.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…When our study is compared with previous studies, the Thymo dosages studied here were lowered and with less complications, yet just as effectual [11][12][13][14][15][16][17]. In summary, induction therapy with either Thymo regimen for three consecutive days, with maintenance of tacrolimus, prednisone and MMF, was safe and successful with no acute rejection episodes or post-transplant complications during 6 months and subsequently at 24 months of follow-up.…”
Section: Discussionmentioning
confidence: 85%
“…For example, previous studies have reported the use of Thymo in dosages ranging from 4.2 to 10.5 mg/kg (total cumulative dose) for induction therapy in adult KTR with variable success [11][12][13][14][15][16][17]. In an attempt to better delineate the degree and durability of T-cell clearance with Thymo, as well as its safety profile, we analyzed our recent experience with the use of two different 3-day regimens of Thymo induction therapy (1.0 vs. 1.5 mg/kg/day) in adult KTR.…”
Section: Discussionmentioning
confidence: 99%
“…In a small, nonrandomized prospective study of 29 African Americans and 20 high-risk Hispanic renal transplant recipients, the addition of the IL-2 receptor antibody daclizumab to CSA, MMF, and prednisone was associated with a reduction in acute rejection rates to 26.4% per patient-years vs. 49.3% in 56 similar controls who did not receive daclizumab with average follow-up of approximately 13 and 17 months, respectively (24). In a retrospective study of 88 AA renal transplant recipients, induction with thymoglobulin (nϭ36) or basiliximab (nϭ52) resulted in comparable graft survival and function at approximately 20 months, though the treatment groups had different composition (25). AA renal transplant recipients treated either with CSA/prednisone (nϭ90) or sirolimus (SIR)/CSA/ prednisone (nϭ86) were compared with 148 white recipients receiving SIR/CSA/prednisone (26).…”
mentioning
confidence: 95%
“…Haririan et al retrospectively analyzed outcomes in 88 African-American kidney recipients receiving induction with rATG (36 patients) or basiliximab (52 patients). 50 The dose of rATG was 1.5 mg/kg daily for 4-7 days and basiliximab was 20 mg on days 0 and 4.The rATG group had significantly more retransplants (44% versus 2%, P , 0.0001), more sensitization (current PRA . 10% in 47% versus 0%, P , 0.0001), and numerically more delayed graft function (50% versus 38%, P = 0.21).…”
Section: Induction: Ratg Use In African-americansmentioning
confidence: 99%